Disfungsi Keluarga dalam Film Aku Tak Membenci Hujan: Relevansinya bagi Konseling Keluarga : Penelitian - Mei Sarri (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to examine the representation of family dysfunction in the film Aku Tak Membenci Hujan and its implications for conceptual understanding in family guidance and counseling. Employing a qualitative approach with film analysis as a cultural text, the study is grounded in Murray Bowen’s Family Systems Theory. The analysis focuses on dysfunctional relational patterns within the family system, including a lack of affective support, unresolved relational conflicts, and avoidance of emotional communication, which contribute to the emergence of emotional cutoff and identity fragmentation in the main character. The findings reveal that emotional cutoff is portrayed as an individual coping strategy in response to chronic anxiety within a dysfunctional family system; however, it is maladaptive, as it reinforces emotional distance and inhibits relational healing. Furthermore, family relational dysfunction contributes to a low level of differentiation of self, reflected in the character’s difficulty separating emotional reactivity from rational functioning. These findings underscore that individual psychological problems cannot be understood independently of broader family system dynamics. This study offers important implications for family counseling practice, particularly emphasizing the need for a systemic approach in addressing relational conflicts and psychosocial trauma experienced by individuals.